Autotransplantation of teeth to the anterior maxilla: A systematic review of survival and success, aesthetic presentation and patient‐reported outcome. Issue 1 (28th November 2017) - Akhlef, Yousra; Schwartz, Ole; Andreasen, Jens O.; Jensen, Simon S.
Abstract: Background/Aim: Autotransplantation of teeth to the anterior maxilla may be indicated after trauma or in patients with congenitally missing teeth. The aim of this systematic review was to report the current evidence concerning survival and success rate, aesthetic outcome, and patient‐reported outcome of autotransplanted teeth to the anterior maxilla. Materials and Methods: A MEDLINE search followed by an additional hand search was performed to identify relevant literature. All levels of evidence except case reports were considered. Any publication reporting on 10 or more autotransplanted teeth to the anterior maxilla, and written in English were eligible for this systematic review. Results: The systematic search identified 95 abstracts. Thirty‐seven full‐text articles were evaluated of which 17 could finally be included. Data on survival and success rate of the transplants could be extracted from 11 studies. Survival rates ranged between 93% and 100% (weighted mean: 96.7%, median: 100%) after 9 months to 22 years of observation (median: 8.75 years). No consensus regarding definition of success criteria of the transplants could be found in the literature. Two and four studies contained data on aesthetic and patient‐reported outcomes, respectively. In general, they reported favourable aesthetic results and high patient satisfaction. Conclusion: The current available evidence suggests a high survival rate after autotransplantation of teeth to the anterior maxilla. However, the level of evidence is low. Limited data on aesthetic and patient‐reported outcomes warrant additional research in this field.